Teacher precognitive conditions in the formation of skills for the Formative Research - Viteri, Telmo (Revista Universidad de Guayaquil, 2012)
Meet the demands theoretical and methodological-epistemological matter teaching-learning in relation to socio-economic interpellations-production-cultural country and the world is a mirror where higher education institutions see their successes, failures, and in this sense, we observeevaluate their Teaching-Student, hence, the academic Teacher-Student must be imbued with a scientific attitude, where the teaching of thinking is a psychotherapist and bearing of their programming-academic activities from holistic, systemic, complex, understanding that the individual is a biopsychosocial unit in permanent construction required to achieve a set of knowledge-skillsskills, involve them in problem situations that revolve around a research conducted, the small group work, the exchanges between the equipment and the scientific community represented by the same teaching, research, texts, internet, facing their scientific objects / solving these hypotheses in an effort to reach the seat-edge scientific and academic-democratic-cultural change required in the political processes of our nation in Latin America.